Paradigma Baru bagi Pengkajian Masalah Wanita dan Jender dalam Antropologi - Tapi Omas Ihromi (Antropologi Indonesia, 1999)
In this article the author argues for the need to develop and use a new paradigm in examining the role of women. By considering the significant role women played in the recent economic crisis in Indonesia which has been neglected by various parties, including scholars, the author prefers strongly to use the paradigm 'critics' in the studies about women. She explains further the difference between this paradigm and the 'interpretive' and positivism' paradigms. The use of the new paradigm would enable the researcher to examine the relevant issues, carry out a participative approach, as well as change the disadvantaged situations and roles the women have.